Utilization of Technology in Agricultural Activities in Gunung Tinggi Village, Batulicin District, Tanah Bumbu Regency - Hasanah, Nurul; Sari, Raihanah; Jumriani, Jumriani; Syarifuddin, Syarifuddin; Nur’aini, Fatwa (Program Studi Pendidikan IPS, 2026)
The use of agricultural technology, especially in Gunung Tinggi Village, Batulicin District, is inseparable from agricultural activities and community cooperation . Social studies learning materials can be taken from real life in the community environment, the use of agricultural technology in materials about humans, places, and the environment so that the use of agricultural technology can be used as a source of social studies learning. This study aims to describe the use of technology in agricultural activities in Gunung Tinggi Village, Batulicin District, Tanah Bumbu Regency. This research method uses a qualitative research method to describe the Utilization of Technology in Agricultural Activities in Gunung Tinggi Village, Batulicin District, Tanah Bumbu Regency as a Learning Resource for Social Studies. The subjects in this study are the utilization of technology in agricultural activities, the head of agricultural management, agricultural administrators and members, the head and secretary of the BPP of Tanah Bumbu Regency. Data collection techniques are carried out by observation, interviews, and documentation. Data analysis uses data reduction based on research objectives, data presentation based on descriptions, and data conclusions based on drawing conclusions. Data validity testing is carried out using triangulation techniques. The results of the study obtained that the use of agricultural technology in Gunung Tinggi Village, Batulicin District, Tanah Bumbu Regency, namely Preparation of agricultural wetlands, Preparation of seeds or planting, Fertilization, Maintenance of rice plants, Pest and disease control, and Post-harvest. The conclusion is that agricultural activities in Gunung Tinggi Village have utilized various agricultural technologies, both traditional technologies that have been modernized and modern technologies, such as the use of agricultural tools, land processing systems, and the use of other agricultural support facilities. This technology plays a role in increasing the efficiency and productivity of agricultural products for the local community.